Effet bénéfique d’un arrêt du travail avant l’accouchement - Xu, Qian (Can J Public Health, 2002)
OBJECTIVE: To identify the contribution of the duration of the prenatal maternity leave on term delivery. METHOD: Characteristics of the prenatal maternity leave and delivery among 363 working women who had delivered a full-term infant at 1 of 4 hospitals in Montreal during 1996 were studied. RESULTS: The presence of an intervention or complication during delivery was observed in 68.9% of the participants. The average duration of the prenatal maternity leave was about 8 weeks (SD = 7). The adjusted risk of a difficult delivery decreased significantly with the duration of the prenatal maternity leave (OR = 0.96; 95% CI: 0.93 - 0.99). CONCLUSION: The duration of the maternity leave before delivery is associated with an easier term delivery for working women.